2022
DOI: 10.1021/acscatal.1c05512
|View full text |Cite
|
Sign up to set email alerts
|

Role of Brønsted Acids in Promoting Pd(OAc)2-Catalyzed Chlorination of Phenol Carbamates Using N-Chlorosuccinimide

Abstract: Numerous studies have demonstrated that Brønsted acids (HAs), such as HOTf and HOTs, can promote Pd(OAc) 2catalyzed functionalization of C−H bonds. However, the rationale for using these acids as a promoter is not yet completely obvious. The purpose of this work is to provide a detailed explanation for this observation with the aid of density functional theory calculations. This is accomplished by investigating the chlorination mechanism of phenol carbamates (DG∼C−H) with N-chlorosuccinimide (NCS) using HOTf a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…It was found that the major donor–acceptor interaction involved in TS3a is the electron donation from the d z 2 -type orbital of the Pd center to the σ*­(C–I)-type orbital of iodide (Figure a). A similar donor–acceptor interaction was proposed by Ariafard and co-workers in an S N 2-type oxidative addition TS of a phenol carbamate-derived palladacycle complex with N -chlorosuccinimide . In contrast, in TS3c , both the donation from the Pd d z 2 -type orbital to σ*­(C–I)-type orbital and the back donation from the nonbonding electron pair of iodine to the empty d x 2 – y 2 -type orbital of Pd are significant, with the latter being more profound (Figure b)…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It was found that the major donor–acceptor interaction involved in TS3a is the electron donation from the d z 2 -type orbital of the Pd center to the σ*­(C–I)-type orbital of iodide (Figure a). A similar donor–acceptor interaction was proposed by Ariafard and co-workers in an S N 2-type oxidative addition TS of a phenol carbamate-derived palladacycle complex with N -chlorosuccinimide . In contrast, in TS3c , both the donation from the Pd d z 2 -type orbital to σ*­(C–I)-type orbital and the back donation from the nonbonding electron pair of iodine to the empty d x 2 – y 2 -type orbital of Pd are significant, with the latter being more profound (Figure b)…”
Section: Resultsmentioning
confidence: 97%
“…A similar donor−acceptor interaction was proposed by Ariafard and coworkers in an S N 2-type oxidative addition TS of a phenol carbamate-derived palladacycle complex with N-chlorosuccinimide. 33 -type orbital of Pd are significant, with the latter being more profound (Figure 4b). 34 Based on the above analysis, we conclude that the σdonation ability of the ligands is a key factor affecting the alkylation mechanism, which is supported by the computed energy levels of the palladacycles of interest (Figure 5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Similar donor-acceptor interaction was proposed by Ariafard and co-workers in an S N 2-type oxidative addition TS of a phenol carbamate-derived palladacycle complex with N-chlorosuccinimide. 30 In contrary, in TS3c both the donation from the Pd d z 2 -type orbital to σ*(C-I)-type orbital and the back donation form the nonbonding electron pair of iodine to the empty d x 2y 2 -type orbital of Pd are significant, with the latter being more profound (Figure 3b). Based on the above analysis, we purpose that the σ-donation ability of the ligands is a key factor affecting the alkylation mechanism, which is supported by the computed energy levels of the palladacycles of interest (Figure 4).…”
Section: Scheme 4 Stereochemical Investigation On Palladacycle Complexmentioning
confidence: 92%
“…All DFT calculations were performed using Gaussian 16 at the M06-L level of theory . The accuracy of M06-L in calculating the energy of organometallic reactions has been shown in numerous studies. For all the calculations, solvent effects were considered using the SMD solvation model with water as the solvent. The SDD basis set , with effective core potential was chosen to describe iron.…”
Section: Computational Detailsmentioning
confidence: 99%